Approche pragmatique du droit de l'État de punir - Manganas, Antoine (Les Cahiers de droit, 1986)
The author trys to find some rational justifications for the power of the State to impose penal sanctions. He explains why in some exceptional situations the mecanisms of the penal system cannot be replaced by other alternatives. The State has to maintain its power to impose penal sanctions in three particular cases : in the case of dangerous offenders such as multirescidivists : in the case of persons who are not willing to execute the « alternative » measures ; and, most important, in the case of new offenses like impaired driving or crimes against the environment where the state has to be very tough. These are crimes of great danger for society and the offenders are often conscious of the dangerous nature of their conduct.